(untitled) (Marketing Journal, 2026)
Abstract The article examined the development of investment activity of industrial enterprises based on lean production principles. The investment potential of enterprises in the oil and fat industry was assessed considering production, financial, innovative, and labor factors. Optimization of production processes and reduction of losses were substantiated as conditions for improving investment efficiency. The state of the raw material base and modernization directions of the industry were analyzed. The necessity of applying operational performance indicators in evaluating investment projects was demonstrated. Digitalization and technological renewal were identified as factors enhancing investment attractiveness. Based on the research findings, practical recommendations were developed to increase investment activity and ensure sustainable development of enterprises. Keywords: industry, enterprise, potential, investment, investment attractiveness, enterprise investment potential assessments, investment policy.